Naguvanahaili screening - NS, Vishwanath; MN, Nagaraj; CV, Swamy Sridhar; HS, Satyan (Journal of All India Institute of Speech and Hearing, 1971)
This is a report on the collaborative project with the Junior Jaycees of Mysore to screen the school going children for speech and hearing problems in a nearby village. This village, was selected because of the following reasons.